Bioethics and the argumentative legacy of atrocities in medical history: Reflections on a complex relationship. (3rd January 2021) - Schicktanz, Silke; Michl, Susanne; Stoff, Heiko
Abstract: Slippery slope‐, taboo‐breaking‐ or Nazi‐analogy‐arguments are common, but not uncontroversial examples of the complex relationship between bioethics and the various ways of using historical arguments in these debates. In our analysis we examine first the relationship between bioethics and medical history both as separate disciplines and as argumentative practices. Secondly, we then analyse six common types of historical arguments in bioethics (slippery slope‐, analogy‐, continuity‐, knockout/taboo‐, ethical progress‐ and accomplice‐arguments), some as arguments within the academic debate of bioethics, others as arguments within political and public debates over bioethical issues. We conclude by suggesting to bioethicists to better understand historical arguments as socially and culturally embedded practices of critical reflection of power, medical and government paternalism and possible future scenarios. More interdisciplinarity between ethicists and medical historians is needed to appropriately rationalize and understand the different legacies.